Teen Guide to Homemaking - Brinkley, Jeanne Hayden; Chamberlain, Valerie M.; Champion, Frances 1909-1987. (New York : Webster Division, McGraw-Hill, 1977)
A textbook planned to assist teen-age boys and girls in assuming responsibilities in the home. Provides guidelines for family living, making decisions, clarifying values, budgeting, personal grooming, and cooking.
Includes index.
Keywords: Home economics; Home economics